Grabbing readers: how to focus your paper's title and contents on its major theoretical contribution rather than the local context of the study - Woodside, Arch (Taylor & Francis, 2015)
Which of the following two titles did the author(s) of the journal article or book actually use: (A) Client-Hairdresser Conversations in the Beauty Salon Industry in Metropolitan Regions of Turkey or (B) How Marketplace Performances Produce Interdependent Status Games and Contested Forms of Symbolic Capital (U-¨ stüner and Thompson, 2012)? Here are two additional titles to select one from: (A) Meetings and Pastimes of Young Male Friends in the North End of Boston or (B) Street Corner Society (Whyte, 1943). This chapter offers a primer on writing titles and relating the scholarly content of your academic paper to contribute original theory to a discipline and get your paper accepted for publication. The chapter offers tenets—sets of helpful rules for writing titles and paper content—for increasing readers' interest and editors' acceptances of authors' paper submissions for publication in SSCI journals. This chapter focuses on 10 useful rules of thumb to consider when writing a title for a paper that you plan to submit for publication consideration to an editor of a scholarly journal in the behavioral sciences including more than 16 subcategories of journals in the general field of business, economics, and management. Combining these 10 rules provides an algorithm (a checklist; see Gawande [2010] on the value of checklists) designed to be useful for increasing clarity and the attention, understanding, and acceptance that your paper receives by the editor and, one hopes, reviewers.